A nationwide web-based survey of factors associated with depressive symptoms among Japanese workers. (August 2022) - Saito, Shota; Qi, Ruan; Tran, Huyen Thi Thanh; Suzuki, Kenji; Takiguchi, Toru; Noto, Shinichi; Ohde, Sachiko; Takahashi, Osamu
Background: Precarious employment has affected mental health, and limited data are available on the association of low stress tolerance with depressive symptoms among Japanese workers. Aims: This study aimed to examine the relationship between stress tolerance and depressive symptoms among Japanese workers, including company employees, civil servants and self-employed persons in various industries. Methods: We conducted a nationwide cross-sectional study. From March 26 to April 6, 2020, we performed a web-based survey of Japanese workers. The questionnaire included questions on socioeconomic factors, the SOC scale that assesses stress tolerance, the CES-D, and the EQ-5D-5L. Multivariate regression analyses were performed to determine the factors associated with depressive symptoms. Results: We included 3, 001 participants in the analysis. A high SOC score, adequate sleeping time and frequency of exercise were associated with higher depressive symptoms. Employment status and long working hours were not associated with depressive symptoms. Younger workers had lower SOC scores than older workers. An inverse correlation between the SOC score and CES-D score was found among Japanese workers. Conclusions: Improving stress tolerance among younger workers is needed to prevent worsening mental health regardless of employment status for Japanese workers.